On the convenience of admitting and regulating premarital and marital agreements - Vega Mere, Yuri (2014)
Nothing much has changed in the Law of Family in Peru. The main doctrine argues that it is not possible to make agreements between spouses on non-economic aspects of their relationships or their duties with their children, even when they could make decisionsin a more convenient way.In the article, the author argues that it is desirable to relax the rules on agreements between spouses or prospective spouses to regulate their rights during marriage or the benefits and obligations of each one in case they end their marriage. In that way, the author alludes to the figures of prenuptial and marital agreements present in American reality.